2013
DOI: 10.1111/zph.12057
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Streptococcus dysgalactiae subsp. equisimilis between Child and Dog in an Aboriginal Australian Community

Abstract: Streptococcus dysgalactiae subsp. equisimilis (SDSE), also known as group G and C streptococci, is becoming increasingly recognized as a pathogen in humans. We report here the finding of an identical strain of SDSE in the throat of a child and their dog in an Aboriginal Australian community. The strain was identified using the API 20Strep system, 16S rRNA gene sequencing, emm sequence typing (emmST) and multilocus sequence typing (MLST) as a group C SDSE, stC839.5 and ST-3. Carriage of this strain by a human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…The association of BHS carriage with rural residence was driven by GCS. Further studies are needed to define streptococcal reservoirs beyond the human pharynx; isolated reports on cross-species transmission between humans and pets [15] may indicate a possible role of animals underlying increased carriage rates with rural residence. As anticipated, antibiotic drug intake in the preceding month did not influence GAS carrier status in our cohort underlining ineffectiveness of antibiotics for sustained eradication of streptococcal carriage.…”
Section: Discussionmentioning
confidence: 98%
“…The association of BHS carriage with rural residence was driven by GCS. Further studies are needed to define streptococcal reservoirs beyond the human pharynx; isolated reports on cross-species transmission between humans and pets [15] may indicate a possible role of animals underlying increased carriage rates with rural residence. As anticipated, antibiotic drug intake in the preceding month did not influence GAS carrier status in our cohort underlining ineffectiveness of antibiotics for sustained eradication of streptococcal carriage.…”
Section: Discussionmentioning
confidence: 98%
“…dysgalactiae was suggested for the animal isolates. Nevertheless, an SDSE strain (group C; ST3) was detected colonizing both a dog and child in the same household in an aboriginal community in Australia, illustrating the potential for crosstransmission between humans and animals (Schrieber et al, 2014). Analysing a small collection of SDSE isolates from equines at a farm located in Seropédica, we found that three of the isolates clustered in clone B.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described the isolation of an identical strain colonizing the oropharynx of a child and dog from the same household in an aboriginal community in Australia. However, no infectious process was reported in either the child or pet (Schrieber et al, 2014). To better understand the epidemiological aspects of SDSE infections, it is important to trace the occurrence and spread of possible well-adapted SDSE clones.…”
Section: Introductionmentioning
confidence: 99%
“…It is classically considered a commensal of mucosae and the burden of disease is under recognized (16). Transmission from sites of colonization and infections are the main transmission mechanisms, zoonosis is also being described (17,18). SDSE bacteremia is uncommon in children (19); among adults almost all patients have an underlying disease.…”
Section: Discussionmentioning
confidence: 99%